Letter - Brass and General Metal Founders Society, 7 May 1926
1926-05-07 "Letter - Brass and General Metal Founders Society, 7 May 1926" [g0646001.jpg], 7 May 1926, Brass and General Metal Founders Society Union Reports and Correspondence